PELATIHAN PEMOGRAMAN LARAVEL PADA SISWA SMA IT PLUS BAZMA BRILLIANT - Nur Budi Nugraha; Tri Handayani; Tri Yuliati; Ari Sellyana (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2021)
The corona virus outbreak affects various aspects of life, including the field of education. SMA IT Plus Bazma Brilliant during the online learning period has used e-learning in its teaching and learning activities. Teachers in utilizing information technology, must be creative. The number of students who want to learn programming laravel framework to make applications so that they learn through social media ranging from youtube, facebook or links on google. However, even though they are learning on their own, students still find it difficult because there is no teacher to guide them. There are some students who don't really understand programming, one of which is Laravel programming because of the lack of direct assistance during this COVID-19 pandemic. The purpose of this service is to provide training to students in understanding Laravel framework programming. The method used is through lectures and discussions followed by direct practice using the Laravel framework which is guided by the service team. The results of this service. Participants who took part in the training felt happy and satisfied with this service activity, this could be seen from the expressions of satisfaction and enthusiasm of the participants listening and asking various things about the material that had been given by the devotees. This service activity is considered by the participants as a means of introducing and learning the Laravel framework as a basis for learning programming to create a simple project